2010
DOI: 10.1186/1472-6882-10-35
|View full text |Cite
|
Sign up to set email alerts
|

The use of complementary and alternative medicine by patients with diabetes mellitus in Bahrain: a cross-sectional study

Abstract: BackgroundCAM use is widespread, especially among patients with diabetes. The Gulf States have a high prevalence of diabetes, alongside a long tradition of CAM use. The aim of this study is to establish the prevalence of CAM use among patients with diabetes mellitus in Bahrain and to examine the characteristics of the CAM users.MethodsA questionnaire was developed and administered to a convenience sample of patients with diabetes (n = 402) above the age of 20 attending two hospital diabetes clinics. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
54
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 10 publications
(14 reference statements)
11
54
1
4
Order By: Relevance
“…Çalışmamıza katılan hastaların TAT kullanım oranlarının %48.1 olduğu belirlenmiştir Ülkemizde yapılan çalışma-larda, diyabetli hastalarda TAT kullanma oranları %18.5-70.5 (5,12,20,21); farklı ülkelerde yapılan çalışmalarda ise diyabetli hastalarda TAT kullanım oranları %38.1-63 arasında değişmektedir (22)(23)(24). TAT kullanım oranları arasındaki bu farklılığın, yaşanılan toplumun TAT'a iliş-kin değerlerinin, inançlarının, kültürel özelliklerinin ve TAT kapsamında düşündükleri uygulamaların farklı olmasından kaynaklandığı belirtilmektedir (5,22,23).…”
Section: Discussionunclassified
“…Çalışmamıza katılan hastaların TAT kullanım oranlarının %48.1 olduğu belirlenmiştir Ülkemizde yapılan çalışma-larda, diyabetli hastalarda TAT kullanma oranları %18.5-70.5 (5,12,20,21); farklı ülkelerde yapılan çalışmalarda ise diyabetli hastalarda TAT kullanım oranları %38.1-63 arasında değişmektedir (22)(23)(24). TAT kullanım oranları arasındaki bu farklılığın, yaşanılan toplumun TAT'a iliş-kin değerlerinin, inançlarının, kültürel özelliklerinin ve TAT kapsamında düşündükleri uygulamaların farklı olmasından kaynaklandığı belirtilmektedir (5,22,23).…”
Section: Discussionunclassified
“…In Tunisia, Libya's immediate neighbour, a clinic-based study among diabetes patients reported 23% of patients used herbal remedies for blood sugar control (11). However, higher figures were found among diabetic patients in other Arab countries, such as 41.7% in Egypt (27), 51.9% in Palestine (10), 63% in Bahrain (16) and 54.8% in Morocco (28). Generally, the differences in the definition of traditional medicine use across studies prevent precise comparisons of traditional medicine use rates.…”
Section: Discussionmentioning
confidence: 99%
“…These include practices like al-hijama (wet cupping), and al-ruqyah, which is an Islamic-based spiritual practice usually done by reciting some verses from the Quran or dua (supplications) from the sunnah. Correspondingly, prevalent use of traditional medicine by diabetes patients has been reported in some Arab countries (16)(17)(18). The Middle East and North Africa region has the highest estimate rate of diabetes in the world (19).…”
Section: Introductionmentioning
confidence: 99%
“…In the study performed by Neto et al (2009), it was concluded that use of complementary and alternative medicine had a positive relationship with gender, territory, income, educational and marital status. In the study performed by Khalaf and Whitford (2010) concerning the use of CAM among patients with diabetes, it was found that in the two diabetes clinics in Bahrain, the use of CAM among patients with diabetes was profoundly high. In the study performed by Richmond et.…”
Section: Introductionmentioning
confidence: 99%